(untitled) (Revista Rupturas, 2017)
The current document addresses the discussion about the social construction of space, specifically about the production of public space in an ephemeral space-time within the urban structure as the farmer’s market. It seeks to defend the premise that public space will be appropriate; used; that convenes and dynamizes the city without necessarily being a space defined and conceived for such purposes. The work is constructed through observations and interviews at the farmer’s market in the Heredia´s Central Canton, as well as triangulations with various theoretical references.